Structure evolution in the reduction process of FeO powder by hydrogen - YANG Xiao-bo; HU Xiao-jun; CHEN Zhi-yuan; DANG Jie; FANG Fei; ZHOU Guo-zhi (工程科学学报, 2015)
The isothermal hydrogen reduction kinetics of FeO powder at 773-1273 K was investigated by thermogravimetry. Above 873 K, there was a turning point in the kinetic curve, which indicated that the reduction mechanism changed. An unusual temperature effect that the reduction rate decreased with increasing temperature was observed from 973 K to 1073 K. To discuss the effect of product structure on the reduction rate of iron oxide, the morphology of samples reduced at different temperatures and for different reaction time was observed by scanning electron microscopy. It was shown that holes on the sample surface increased gradually, the dendritic characteristic appeared with increasing temperature, and the sintered phenomenon was obvious at 973 K and 1023 K. At a certain temperature, holes on the sample surface increased and the sintered phenomenon appeared gradually with prolonging reaction time. At 973 K and 1023 K, the sample kept fairly the original shape, but at 1173 K, just reacted for 2 rain, a large number of dendritic products appeared and sintered gradually. Combining the morphology and kinetic curves, it can be summarized that interfacial chemical reaction is the rate-limiting step in the initial stage of hydrogen reduction. But as the reaction proceeds, the reduced iron sinters and the compact structure of the reduced product hinders the outward diffusion of produced gas. The rate-limiting step changes to the outward diffusion of produced gas, which leads to the decrease of the reduction rate of iron oxide by hydrogen.